Kontribusi Praktik Kerja Industri dan Mata Pelajaran Prakarya dan Kewirausahaan Terhadap Sikap Kewirausahaan Pada Siswa Kelas XI Jurusan Akuntansi Di SMK Negeri 1 Karanganyar Tahun Ajaran 2015/2016 - Saputra, Arif Angga, Drs. Nur Chusni, SE., M.Ag, Drs. Sudarto, M.M (2016)
ABSTRACT Arif Angga Saputra, A210120051. Contributions Employment Practices Industry and Entrepreneurship Subjects craft and Attitude Toward Entrepreneurship In Class XI student of Accounting Department at SMK Negeri 1 Karanganyar in Academic Year 2015/2016. Study Program of Accounting Education, the Faculty of Education, University of Muhammadiyah Surakarta, July 2016 This study aims to determine: 1) The contribution of the industrial working practices entrepreneurial attitude, 2) Contributions subjects craft and entrepreneurial attitude towards entrepreneurship, 3) Contribution of working practices and subjects craft industries and entrepreneurial attitude towards entrepreneurship. This study is quantitative descriptive research by drawing conclusions through statistical methods. The population in this study is a class XI student of Accounting Department of SMK Negeri 1 Karanganyar totaling 108 students and the sample is 84 students. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability test. Data analysis technique used is multiple linear regression analysis, t-test, F, koefisiens determination (R ²) and partial coefficient of determination (r²). The results of the regression analysis obtained regression equation: Y = 4.277 + 300X1 + 0,419X2. The equation shows that the entrepreneurial attitude is influenced by employment practices and subjects craft industry and entrepreneurship. The conclusions drawn are: 1) Practice industry work towards an entrepreneurial attitude can be accepted. It is based on regression analysis (t test) note that tcount > t table is 2,705 > 1,989 and the significance value < 0.05 is 0,008 with partial determination coefficient of 11.205%. 2) Subjects craft and entrepreneurial attitude towards entrepreneurship can be accepted. It is based on regression analysis (t test) note that tcount > t table is 3.905 > 1.989 and the significance value < 0.05 is 0,000 with partial determination coefficient of 19.149%. 3) work practices and subjects craft industry and entrepreneurial attitude towards entrepreneurship can be accepted. This is based on multiple regression analysis of variance (F test) is known that F count > F table that is 17.652 > 3.11 and a significance value < 0.05 is 0.000. 4) The coefficient of determination (R2) of 0.304 indicates that the contribution of working practices and subjects craft industry and entrepreneurial attitude towards entrepreneurship is 30.4%, while the rest influenced by other variables.